2020
DOI: 10.1080/00365521.2020.1720281
|View full text |Cite
|
Sign up to set email alerts
|

Inter-reader agreement of interpretation of radiological course of bile duct changes between serial follow-up magnetic resonance imaging/3D magnetic resonance cholangiopancreatography of patients with primary sclerosing cholangitis

Abstract: Kartalis (2020) Inter-reader agreement of interpretation of radiological course of bile duct changes between serial follow-up magnetic resonance imaging/3D magnetic resonance cholangiopancreatography of patients with primary sclerosing cholangitis, Scandinavian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Poor agreement between readers in the evaluation of MRI of patients with PSC is well known. The results of our study are in line with two previously performed studies evaluating interreader agreement of MRI/ MRCP examinations in patients with PSC, although these studies did not specifically evaluate the parameters assessed here [8,9]. Altogether, it can be concluded that evaluation of the MRI/MRCP of patients with PSC is challenging.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Poor agreement between readers in the evaluation of MRI of patients with PSC is well known. The results of our study are in line with two previously performed studies evaluating interreader agreement of MRI/ MRCP examinations in patients with PSC, although these studies did not specifically evaluate the parameters assessed here [8,9]. Altogether, it can be concluded that evaluation of the MRI/MRCP of patients with PSC is challenging.…”
Section: Discussionsupporting
confidence: 88%
“…Although the two ANALI scores seem promising, their interreader agreement has not been evaluated to date. Interpretation of MRI examinations of patients with PSC is challenging, as shown by two recent studies [8,9]. Agreement therefore needs to be assessed before the ANALI scores can be utilized in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…( 7 ) Similarly, interobserver agreement for bile duct changes between two serial follow‐up MRI‐MRCP examinations was also poor, with ICC values ranging between −0.45 and 0.22. ( 30 ) It is therefore unsurprising that there is significant variability on the reported prognostic ability of biliary features in predicting clinical outcomes in PSC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the same MRC scanner was used for all cases and negative controls, although some of the positive controls were imaged at an earlier date. The overall quality of MRCs was high, with only 1 of 174 MRC scans needing to be repeated 24 …”
Section: Discussionmentioning
confidence: 99%
“…The overall quality of MRCs was high, with only 1 of 174 MRC scans needing to be repeated. 24 Patients with classical PSC-UC are at a four-fold greater risk of developing CRD or CRC than those with UC alone. 35,36 Because of the increased CRC risk, patients with PSC-UC are enrolled in surveillance programs with annual colonoscopy and biopsies from the time of diagnosis of PSC.…”
Section: Ta B L Ementioning
confidence: 99%